Superiority Claims for Spinal Devices: A Systematic Review of Randomized Controlled Trials. Issue 3 (May 2020) - Golish, S. Raymond; Groff, Michael W.; Araghi, Ali; Inzana, Jason A.
Study Design: Systematic review. Objectives: Superiority claims for medical devices are commonly derived from noninferiority trials, but interpretation of such claims can be challenging. This study aimed to ( a ) establish the prevalence of noninferiority and superiority designs among spinal device trials, ( b ) assess the frequency of post hoc superiority claims from noninferiority studies, and ( c ) critically evaluate the risk of bias in claims that could translate to misleading conclusions. Methods: Study bias was assessed using the Cochrane Risk of Bias Tool. The risk of bias for the superiority claim was established based on post hoc hypothesis specification, analysis of the intention-to-treat population, post hoc modification of a priori primary outcomes, and sensitivity analyses. Results: Forty-one studies were identified from 1895 records. Nineteen (46%) were noninferiority trials. Fifteen more (37%) were noninferiority trials with a secondary superiority hypothesis specified a priori. Seven (17%) were superiority trials. Of the 34 noninferiority trials, 14 (41%) made superiority claims. A medium or high risk of bias was related to the superiority claim in 9 of those trials (64%), which was due to the analyzed population, lacking sensitivity analyses, claims not being robust during sensitivity analyses, post hoc hypotheses, or modified endpoints. Only 4 of the 14 (29%) noninferiority studies provided low bias in the superiority claim, compared with 3 of the 5 (60%) superiority trials. Conclusions: Health care decision makers should carefully evaluate the risk of bias in each superiority claim and weigh their conclusions appropriately.